2010
DOI: 10.1366/000370210792973631
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Automotive Paint Clear Coats by Ultraviolet Absorption Microspectrophotometry with Subsequent Chemometric Analysis

Abstract: Clear coats have been a staple in automobile paints for almost thirty years and are of forensic interest when comparing transferred and native paints. However, the ultraviolet (UV) absorbers in these paint layers are not typically characterized using UV microspectrophotometry, nor are the results studied using multivariate statistical methods. In this study, measurements were carried out by UV microspectrophotometry on 71 samples from American and Australian automobiles, with subsequent chemometric analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Association and classification of paint samples using HCA, PCA, and discriminant analysis has also been demonstrated (Liszewski et al, 2010;Muehlethaler et al, 2011;Maric et al, 2014). Maric et al analyzed the primer surface layer in automotive paints using synchrotron FTIR (Maric et al, 2014).…”
Section: Trace Evidencementioning
confidence: 93%
“…Association and classification of paint samples using HCA, PCA, and discriminant analysis has also been demonstrated (Liszewski et al, 2010;Muehlethaler et al, 2011;Maric et al, 2014). Maric et al analyzed the primer surface layer in automotive paints using synchrotron FTIR (Maric et al, 2014).…”
Section: Trace Evidencementioning
confidence: 93%
“…Recent studies by Liszewski [12] and Mendlein [13] found that clear coats could be differentiated into broad classes based on their UV microspectrophotometry or micro Raman spectra with chemometric analysis, although they were unable to correlate the separation of samples with the make, model or year of vehicle manufacture. Several publications by Lavine [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Since publication of this report, there has been increasing interest in applying multivariate statistical procedures to forensically relevant chromatographic and spectral data. For example, principal components analysis (PCA), cluster analysis, and discriminant analysis have been applied in the analysis of fire debris [2][3][4][5], explosives [6], controlled substances [7][8][9], and various trace evidence types including hair [10], soil [11], electrical tape [12], and paint [13][14][15]. Forensic research in this area has conclusively demonstrated the potential of these procedures for case work.…”
Section: Introductionmentioning
confidence: 99%